1999
DOI: 10.1002/(sici)1098-2795(199906)53:2<159::aid-mrd5>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Offspring born from chimeras reconstructed from parthenogenetic and in vitro fertilized bovine embryos

Abstract: Chimeric embryos were produced by aggregation of parthenogenetic (Japanese Red breed) and in vitro fertilized (Holstein breed) bovine embryos at the Yamaguchi Research Station in Japan and by aggregation of parthenogenetic (Red Angus breed) and in vitro fertilized (Holstein breed) embryos at the St. Gabriel Research Station in Louisiana. After embryo reconstruction, live offspring were produced at each station from transplanting these embryos. The objective of this joint study was to evaluate the developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Also there is a higher percentage of apoptosis in the haploid PA-embryos after Day 6 in culture, relative to IVF embryos, and there is a trend of an increased incidence of apoptosis during development in vitro . Boediono et al (1999) reported live chimeric calves born after the presumably diploid parthenotes were aggregated with fertilization-derived embryos; thus a possibility remains that with the proper sequence of oocyte activating stimuli, diploid parthenotes with a higher developmental potential can be obtained.…”
Section: Chromosomal Abnormalities and Embryo Developmentmentioning
confidence: 99%
“…Also there is a higher percentage of apoptosis in the haploid PA-embryos after Day 6 in culture, relative to IVF embryos, and there is a trend of an increased incidence of apoptosis during development in vitro . Boediono et al (1999) reported live chimeric calves born after the presumably diploid parthenotes were aggregated with fertilization-derived embryos; thus a possibility remains that with the proper sequence of oocyte activating stimuli, diploid parthenotes with a higher developmental potential can be obtained.…”
Section: Chromosomal Abnormalities and Embryo Developmentmentioning
confidence: 99%
“…Nevertheless, parthenote-derived stem cells can contribute to research assessing the importance of imprinting gene expression in early development and to autologous cell-based therapy in the female. That some of the epigenetic abnormalities in parthenotes can be overcome was evidenced by the birth of parthenogenetic mice that were themselves reproductively normal [12][13][14][15]. Recent reports in with a nonhuman primate parthenote-derived stem cell line indicated that these cells could differentiated into tyrosine hydroxylase-positive dopaminergic neuronal phenotypes that were capable of long-term survival after engraftment into rat or monkey brains [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Offspring produced with this technique were not identical to one another nor to their parents, as variability is given by the parental counterpart. Moreover, live o ffspring were obtained from chimeras reconstructed from aggregation of parthenogenetic and in vitro fertilized bovine embryos (Boediono et al ., 1999). In the rabbit, oviductal transfer of reconstructed zygotes resulted in 100% pregnancy on day 12, but no pregnancies were diagnosed on day 21 after ovulation (Escribá et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%